2009
DOI: 10.1212/wnl.0b013e3181a6b2f8
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameter update: Management issues for women with epilepsy—Focus on pregnancy (an evidence-based review): Obstetrical complications and change in seizure frequency

Abstract: Objective: To reassess the evidence for management issues related to the care of women with epilepsy (WWE) during pregnancy, including the risk of pregnancy complications or other medical problems during pregnancy in WWE compared to other women, change in seizure frequency, the risk of status epilepticus, and the rate of remaining seizure-free during pregnancy.Methods: A 20-member committee including general neurologists, epileptologists, and doctors in pharmacy evaluated the available evidence based on a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
2
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(162 citation statements)
references
References 21 publications
10
138
2
12
Order By: Relevance
“…The literature search identified 160 relevant recommendation statements from 19 guidelines [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and 2 consensus papers. [32][33] Review by the co-chairs and facilitator resulted in 20 recommendation statements that were rated highest on importance, validity, strength of evidence, and gaps in care to serve as the evidence base for 12 candidate measures.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 160 relevant recommendation statements from 19 guidelines [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and 2 consensus papers. [32][33] Review by the co-chairs and facilitator resulted in 20 recommendation statements that were rated highest on importance, validity, strength of evidence, and gaps in care to serve as the evidence base for 12 candidate measures.…”
Section: Resultsmentioning
confidence: 99%
“…Epileptic women are also on slightly increased risk of certain pregnancy complications other than seizures [15]. In a Swedish study of 1207 epileptic women, Pilo and colleagues reported a 1.5-fold increase in the incidence of cesarean delivery, preeclampsia, and postpartum hemorrhage [16].…”
Section: Discussionmentioning
confidence: 99%
“…They are further subcategorized as tonic-clonic (or grand mal), absence (petit mal), myoclonic, or atonic seizures. [27][28][29][30] Tonic-Clonic (Grand Mal) Seizures: The first stage of a grand mal seizure is called the tonic phase, in which the muscles suddenly contract, causing the patient to fall and lie stiffly for about 10 -30 seconds. Spasms occur for about 30 seconds to 1 minute.…”
Section: Generalized Seizuresmentioning
confidence: 99%